2023
DOI: 10.1007/s11356-023-26193-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection with acanthocephalans increases tolerance of Gammarus roeselii (Crustacea: Amphipoda) to pyrethroid insecticide deltamethrin

Abstract: Crustacean amphipods serve as intermediate hosts for parasites and are at the same time sensitive indicators of environmental pollution in aquatic ecosystems. The extent to which interaction with the parasite influences their persistence in polluted ecosystems is poorly understood. Here, we compared infections of Gammarus roeselii with two species of Acanthocephala, Pomphorhynchus laevis, and Polymorphus minutus, along a pollution gradient in the Rhine-Main metropolitan region of Frankfurt am Main, Germany. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…laevis is a typical fish parasite. Both parasite species utilize amphipods and fish as intermediate hosts ( Romanovski, 1964 ; Itämies et al, 1980 ; Gaillard et al, 2004 ; Kochmann et al, 2023 ). The presence of both parasite species in the examined raccoons suggests that they must have preyed on infected amphipods, waterfowl, or fish in the study areas, even if no direct evidence of such species was found in the stomach or intestine, except for the rainbow trout Oncorhynchus mykiss in Hesse ( Table 3 ) ( Itämies et al, 1980 ; Piróg et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…laevis is a typical fish parasite. Both parasite species utilize amphipods and fish as intermediate hosts ( Romanovski, 1964 ; Itämies et al, 1980 ; Gaillard et al, 2004 ; Kochmann et al, 2023 ). The presence of both parasite species in the examined raccoons suggests that they must have preyed on infected amphipods, waterfowl, or fish in the study areas, even if no direct evidence of such species was found in the stomach or intestine, except for the rainbow trout Oncorhynchus mykiss in Hesse ( Table 3 ) ( Itämies et al, 1980 ; Piróg et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [140] collected water grab samples between July 2015 and July 2016 in eight sampling campaigns at 13 sites of the river Horloff which are identical with sites 3-5, 14-21, 23 and 25 in our study. These samples were analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) for 161 medium polar emerging pollutants (54 pharmaceuticals, 18 biocides and pesticides, 10 industrial compounds, 4 X-ray contrast media, 3 artificial sweeteners, 2 corrosion inhibitors, 1 repellent, 1 aversive agent and 1 stimulant), including 67 transformation products.…”
Section: Water Phasementioning
confidence: 99%
“…As an integrative measure for the potential toxicity caused by these compounds, the authors calculated in a first step toxic units (TUs, dimensionless) for those 57 of the 161 analyzed compounds with available toxicity data by dividing the arithmetic mean concentration from all sampling campaigns at a given site for the respective compound by its 50% effect concentration (EC 50 ) for immobilization in acute tests with daphnids. According to the concentration addition concept of [141] the authors calculated in the second step the potential mixture toxicity as the sum of the individual TUs at a given station (see [140] for details).…”
Section: Water Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Like many other amphipods, G. roeselii sensu lato is expected to play a key role as a leaf shredder in the nutrient circle ( Jourdan et al, 2016 ) and can occur in high densities ( Karaman & Pinkster, 1977 ). Both in Central Europe and in the Balkans, G. roeselii sensu lato colonize different habitat types ( e.g ., lakes, mountain streams, rivers) and can also occur in habitats that are heavily anthropogenically stressed ( Jourdan et al, 2019 ; Kochmann et al, 2023 ). So far, G. roeselii sensu lato is considered to have a high tolerance to many environmental conditions and pollution ( Gergs, Schlag & Rothhaupt, 2013 ; Jourdan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%